Day 2 -1420 - Hope.pdf - Gill, Philip (Cranfield University, 2023)
Effects of Energetic Plasticiser Impurities in the Formulation of NC-based Binders and their removal via a Thermal and Chemical Treatment Harry Hope - AWE 9th International Nitrocellulose Symposium Presentations
Keywords: 'nitrocellulose'